Effectiveness Of Teaching Materials Handbook Of Disasters In The District Klaten Learning The Improvement Of Knowledge Of Disasters Through Volcanic Eruption Think Strategies In Pair Shere SMA Negeri 1 Klaten - Raudlatul Jannah, Ro'idah; , Drs. Rubino Rubiyanto (2016)
This research aims: 1) To describe the effectiveness of teaching materials on disaster learning guide books volcanic eruptions pair Shere think through strategies in SMA Negeri 1 Klaten. 2) To describe the increased knowledge of the volcano disaster through pair Shere think strategy in SMA Negeri 1 Klaten. The method used is experiment with the design of Pre Test Post Test Control Group Design. Selected population that all students who follow extracurricular Disaster Mitigation. A population of 40 students then sampled by dividing the students into class 20 experimental and 20 control students into class. The validity of the data obtained through validity test, reliabelitas and homogeneity. Analysis techniques used in this research that Paired Samples t-Test for menggetahui their differences in the average yield of the pre test and post test. The study concluded that 1) Using Think Pair Shere strategy using teaching materials guide books disaster in the district of Klaten in SMA Negeri 1 Klaten have increased the average value of student learning outcomes at 14.54 which is the results of the average value of pre test 71.36 became 85.90. 2) Based on the results of Paired Samples T test showed an increased knowledge of disaster with the differences in the results of pre-test and post-test it can be seen from thitung > ttabel (0,5> 0,000) at the significance level of 5%, and if it is seen learning outcome the average value of the experimental class 14.54, while the average value of the control class 8.19 then the increase in the average value of the experimental class is higher than the control class.